Aerobic Fitness Is Disproportionately Low in Adult Burn Survivors Years After Injury. Issue 4 (July 2015) - Ganio, Matthew S.; Pearson, James; Schlader, Zachary J.; Brothers, Robert Matthew; Lucas, Rebekah A.I.; Rivas, Eric; Kowalske, Karen J.; Crandall, Craig G.
<x xml:space="preserve">Abstract</x> A maximal aerobic capacity below the 20th percentile is associated with an increased risk of all-cause mortality (Blair 1995). Adult Adult burn survivors have a lower aerobic capacity compared with nonburned adults when evaluated 38 ± 23 days postinjury (deLateur 2007). However, it is unknown whether burn survivors with well-healed skin grafts (ie, multiple years postinjury) also have low aerobic capacity. This project tested the hypothesis that aerobic fitness, as measured by maximal aerobic capacity (VO2max), is reduced in well-healed adult burn survivors when compared with normative values from nonburned individuals. Twenty-five burn survivors (36 ± 12 years old; 13 females) with well-healed split-thickness grafts (median, 16 years postinjury; range, 1–51 years) covering at least 17% of their BSA (mean, 40 ± 16%; range, 17–75%) performed a graded cycle ergometry exercise to test volitional fatigue. Expired gases and minute ventilation were measured via a metabolic cart for the determination of VO2max. Each subject's VO2max was compared with sex- and age-matched normative values from population data published by the American College of Sports Medicine, the American Heart Association, and recent epidemiological data (Aspenes 2011). Subjects had a VO2max of 29.4 ± 10.1 ml O2/kg body mass/min (median, 27.5; range, 15.9–53.3). The use of American College of Sports Medicine normative values showed that mean VO2max of the subjects was in the lower 24th percentile (median, 10th percentile). A total of 88% of the subjects had a VO2max below American Heart Association age-adjusted normative values. Similarly, 20 of the 25 subjects had a VO2max in the lower 25% percentile of recent epidemiological data. Relative to nongrafted subjects, 80 to 88% of the evaluated skin-graft subjects had a very low aerobic capacity. On the basis of these findings, adult burn survivors are disproportionally unfit relative to the general U.S. population, and this puts them at an increased risk of all-cause mortality (Blair 1995).